Dinâmica da magnetização em filmes finos de Co20Fe60B20 - Mallmann, Tássia Adriane (2021)
In this work, it was realize a ferromagnetic resonance insvestigation in Co20Fe60B20 thin films with diferent thickness between 100 - 2000 nm. The hysteresis curves were obtained with a vibrating sample magnetometer. The samples with thickness between 100 - 300 nm present a weak in plane anisotropy, while the samples with thickness between 800 - 2000 nm are nearly isotropic. The ferromagnetic resonance measurments were performed with a vectorial network analizer and a microstrip line. The impedance of the microstrip charged with the samples were measured from 0,5 up to 5,0 GHz, with an external magnetic field (± 350 ) applied paralely to the sample plane. The resonance frequencies and the line widths were obtained fitting a Lorentzian line shape to the ΔR vs. H experimental curves. The Kittel relation was used to fitting the fr vs. H curves. The anistropy fields values in the fits are in good agreement with those obtained from hysteresis curves (Hk < 50 Oe). The saturation magnetization values are accordingly the literature too. The Gilber damping coefficients were obtained making linear fittings in the ΔH vs. f curves. The thinnest samples present very low damping values (2,5 × 10-3 - 5,0 × 10-3), while in the thickest films (800 and 1600 nm) the values are bigger (12,4 × 10-3 and 18,8 × 10-3). The results shown that is possible to obtain low Gilbert damping thin films without involve any pos-deposition process. The low damping and easy deposition process make this material extremely useful to experiments and applications involving spin waves propagation and spin current injection by FMR.